Liquid crystal dispersions containing nanoparticles of different anisometry: carbon nanotubes and organomodified laponite - Samoilov, A.N.; Minenko, S.S.; Lisetski, L.N.; Solovyova, E.A.; Lebovka, N.I.; Vistak, M.V. (Functional Materials, 2017)
Optical transmission and optical microscopy studies have been carried out for dispersions of organomodified laponite in cholesteric liquid crystal (CLC) matrices. Laponite samples with different degree of exfoliation, obtained by different treatment procedures, were used, with laponite concentration in the dispersions varying from 0.05 to 0.4 %. The results obtained were compared to previously reported data on dispersions of carbon nanotubes in similar experimental conditions. As a general tendency, at low concentrations the nanoparticles tended to accumulate at the CLC texture defects, while at higher concentrations they became dispersed in the anisotropic liquid crystalline structure, with the degree of homogeneity and particle aggregation features depending upon specific features of each case.